Species delimitation and evolutionary relationships among Phoebis New World sulphur butterflies (Lepidoptera, Pieridae, Coliadinae). (4th December 2019) - Núñez, Rayner; Genaro, Julio A.; Pérez‐Asso, Antonio; Murillo‐Ramos, Leidys; Janzen, Daniel H.; Hallwachs, Winnie; Wahlberg, Niklas; Hausmann, Axel
ABSTRACT: The most accepted taxonomic treatment of the New World sulphurs of the genus Phoebis Hübner, [1819] recognizes 16 species including those in the current synonyms Aphrissa and Rhabdodryas . This total conflicts with the results of several recent pierid DNA barcode studies across the Neotropics. We used a five‐locus dataset to carry out species delimitation analyses using the coalescence‐based method implemented in bpp software. After testing the resulting species hypotheses using marginal likelihood estimates, we inferred their phylogenetic relationships and performed an ancestral range reconstruction with biogeobears. Our analyses recovered two different hypotheses, 26 and 24 species, that scored the highest marginal likelihood estimate. Differences between these two hypotheses, when reconciled with barcode clusters and morphology, indicated that 24 is the most likely number of species. Phoebis neocypris stat. rev., Phoebis rurina stat. rev., Phoebis virgo stat. rev., Phoebis marcellina stat. rev., Phoebis thalestris stat. rev., and Phoebis rorata stat. rev. are raised to the species rank. We dated the crown age of Phoebis to the mid‐Miocene, with the islands of the Greater Antilles as the most probable ancestral range. Three main clades of Phoebis diverged early in the evolutionary history of the genus, but most extant species‐level diversity arose after the Pliocene–Pleistocene boundary. Our analyses recovered alternate range expansions and contractions, and dispersal from the islands to the continent and back, in the three main clades. Both sympatric and allopatric speciation seem to have shaped the current species richness. Abstract : Molecular species delimitation in Phoebis butterflies (Lepidoptera: Pieridae) suggests species richness higher than the currently accepted 16 species – 24 species is the most likely hypothesis. Phylogentic reconstructions including all but one species of the genus confirm the status of Aphrissa and Rhabdodryas as synonyms. The analyses recovered three major clades within Phoebis . Phoebis arose during the mid‐Miocene with the Greater Antilles as the most probable ancestral range. Most extant species‐level diversity seems to have evolved after the Pliocene–Pleistocene boundary.